Meta Analisis : Pengaruh Model Pembelajaran Discovery Learning Dalam Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Kurnia Wulansari; Lufri; Zulyusri Zulyusri; Fitri Arsih (Institut Agama Islam Negeri Kerinci, 2021)
The development of the 21st century requires students to master several skills, one of which is critical thinking skills. This study aims to analyze the effect of the Discovery Learning learning model on students' critical thinking skills at various levels. The research method used is a meta-analysis by reviewing 20 journals. The sample in this study came from educational journal articles that have been published nationally and internationally in the last six years (2015-2021). Data collection is done by searching electronic journals through Google Scholar, Academia and Eric. The results of the study show that the Discovery Learning learning model has an effect size value of 1.812 with a high category. This shows that the Discovery Learning learning model has a significant effect on students' critical thinking skills. Keywords: Discovery learning, critical thinking